POLA KOMUNIKASI ANTARA ORANG TUA DAN SISWA KELAS 12 DI WILAYAH JAKARTA UTARA SETELAH DITETAPKANNYA PEMBELAJARAN JARAK JAUH (PJJ) - Sarah Anisa Nurjanah, (2022)
Distance learning is a solution set by the government based on Circular Number 4 of 2020 concerning the implementation of education in an emergency period as an alternative in the world of education in order to reduce the spread of Covid-19. This distance learning makes parents and children interact more often because they often meet at home. Students study online and lose intense time with teachers at school. Meanwhile, as twelfth grades Students have to prepare themselves for various exams and the selection of college majors. This study aims to determine the communication patterns used by parents with twelfth grades Students after the establishment of distance learning. The subjects in this study were five parents and five grade 12 students who live in North Jakarta. This study uses a qualitative method with a phenomenological approach to see the experiences of parents and twelfth grades Students in communicating after the establishment of distance learning. The results of this study indicate that this pandemic has made children and parents closer and more open, and the relationship between them is even closer. The results also show that 1 family applies an authoritarian communication pattern, 1 family applies a permissive communication pattern, 2 families apply a democratic communication pattern and 1 other family applies a paternalist communication pattern. The conclusion that can be drawn from this study is that there is no change in communication patterns that occur under normal circumstances or during a pandemic. Although it is known that there are changes in the nature and emotional side that occur in some individuals.